Conflict Between Public Transportation and Local Community Rights in The Sea - Muchtasar, Rizal; Heriyanti, Heriyanti; Safiuddin, Sahrina; Afoeli, La Ode Muhammad Taufiq (Jurnal Penelitian Hukum De Jure, 2025)
This study aims to analyze the conflict between public access rights and the rights of local communities on Cempedak Island in managing marine areas. The method used is socio-legal, through an analytical approach to national legal frameworks, doctrines, and case studies. The study results show that this conflict creates a dilemma between the interests of local communities and public access rights. The 1945 Constitution and related regulations provide a legal basis for public access rights, but local communities also have rights set out in policies and regulations. This paper critically presents a model of conflict resolution, regulatory, and resource processes that often ignore local community participation. Evaluations of previous Government policy procedures show a lack of consultation and involvement of local communities and public access in policy processes that can result in gaps and prolonged conflicts. This research emphasizes the need for a participatory-collaborative approach. Innovation is the gradual application of the need for community identification to implement comprehensive methods that integrate positive legal analysis with the social and local communities' cultural realities. Conflict techniques on Cempedak Island actively involve communities in decision-making to encourage sustainability, protection, community interests, and public access rights, ultimately creating new policies and rules.